Enzyme Production From Cassava Peels by Aspergillus Awamori KT-11: The Making of Natural Sweetener From Several Tubbers - Melliawati, Ruth; Rahman, Farida (ANNALES BOGORIENSES, 2019)
The use of cassava (Manihot esculenta Crantz) peel for enzyme production has not been widely used. The purpose of this study was to produce complex amylase enzymes from cassava peel by A. awamori KT-11 and apply them in the manufacture of natural sweeteners. Enzyme production is carried out on red and white cassava peel. Media of cassava peel sterilized, inoculated with 1%  A. awamori KT-11, incubated for 5 days, then dried at 50°C and mashed. Making sugar is done on cassava flour, sweet potato ( Ipomoea batatas L), taro (Colocasia esculenta) and cocoyam (Xanthosoma sagittifolium) with different concentrations of 10%, 15%, 20%, and 15% and 20% enzyme concentrations. The hydrolysis process is carried out for 3 days at 60°C. The enzyme activity in red cassava peel was 405,006 U/mL and white cassava peel was 321,239 U/ml. The sugar produced in cassava, taro, sweet potato, and Cocoyam was 101.38 mg/mL, 81.18 mg/mL, 55.929 mg/mL, and 42.874 mg/mL, respectively. The results of TLC showed that cassava and taro sugar  contain maltose, lactose and glucose, sweet potatoes contained glucose and dextrin and Cocoyam containing fructose. The sweetness level of sugar from cassava, taro, sweet potato and Cocoyam is 14 brix, 12 brix, 9 brix and 9 brix, respectively.